The effects of a dentifrice containing zinc citrate and 2,4,4' trichloro-2'-hydroxydiphenyl ether - Saxton, C A (Journal of periodontology (1970), 1986)
The effects of a dentifrice which contained 1% zinc citrate and 0.5% of a nonionic antimicrobial agent, 2,4,4' trichloro-2'-hydroxydiphenyl ether on plaque and gingival health have been investigated. In a 4-day nonbrushing study in which dentifrices were used as slurries, this dentifrice inhibited plaque accumulation significantly more than dentifrices which contained either zinc citrate or Triclosan separately. In a 28-day double-blind cross-over study, a significant reduction in plaque accumulation and improvement in gingival health was demonstrated for the test dentifrice compared to the placebo. The effect was demonstrated with a group of well motivated volunteers who had a good standard of oral health. Analysis of the data suggested that the benefit might be extended to a less motivated population.